2012
DOI: 10.1097/igc.0b013e31825b7de8
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Sarcoma and Aromatase Inhibitors: Tom Baker Cancer Centre Experience and Review of the Literature

Abstract: Aromatase inhibitors are a well-tolerated class of medications that are effective in the treatment of endometrial stromal sarcomas. These medications may also have a role to help stabilize disease progression in the treatment of leiomyosarcoma. More large, prospective, multicentered trials will be needed to clarify this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…33 A recent report, summarizing data on the use of aromatase inhibitors, found an overall response rate of 67% in a total of 28 ESS patients. 32 The data support the current practice in some centers to administer adjuvant hormonal treatment. This seems reasonable, given that hormonal therapies are generally well tolerated.…”
Section: Initial Treatmentsupporting
confidence: 60%
See 1 more Smart Citation
“…33 A recent report, summarizing data on the use of aromatase inhibitors, found an overall response rate of 67% in a total of 28 ESS patients. 32 The data support the current practice in some centers to administer adjuvant hormonal treatment. This seems reasonable, given that hormonal therapies are generally well tolerated.…”
Section: Initial Treatmentsupporting
confidence: 60%
“…31 There is a very high rate of hormone receptor positivity in ESS, up to 100% in some series, 1 which has led to interest in using hormonal therapies for both advanced disease and adjuvant therapy in early-stage disease. 32 The use of adjuvant hormonal therapy has been reported in several studies. A small study reported on 22 patients with ESS, of whom 31% (4/13) of patients receiving adjuvant progestins recurred, compared with 67% (6/9) recurrence in patients who did not receive hormonal therapy.…”
Section: Initial Treatmentmentioning
confidence: 99%
“…Estrogen receptor (ER) and progesterone receptor (PgR) have been detected in 7 --60% and 17 --60% of uterine LMS, thus providing a rationale for the use of aromatase inhibitors in the treatment of these tumors and especially of those with indolent growth [79][80][81][82][83]. Aromatase inhibitors (letrozole, anastrozole or exemestane) obtained a PR in 3 (9%) of 34 patients with measurable, advanced or recurrent uterine LMS, most of whom had previously received at least one chemotherapy line [80].…”
Section: Aromatase Inhibitorsmentioning
confidence: 99%
“…54 Multiple single-institution retrospective analyses provide support for AI, progestin, or GnRH analogue efficacy for treating low-grade ESS. 56,[60][61][62][63][64] A 2012 meta-analysis of the available data from retrospective studies and case reports suggested a 67% overall response rate of ESS to AIs. 62 More recently, studies have generated data to support the efficacy of hormonal therapies for treating hormone receptor-positive uLMS.…”
Section: Hormonal Therapymentioning
confidence: 99%
“…56,65,66 However, other studies have demonstrated more limited response rates for AIs in uLMS, possibly because of the varying degree of hormone sensitivity in these tumors. 62,67…”
Section: Hormonal Therapymentioning
confidence: 99%